Peningkatan Sarana dan Prasarana Pendidikan di Desa Sugarang Bayu - Rizky Habibi Matondang; Siti Nurhaliza (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The improvement of educational facilities and infrastructure is a crucial factor in enhancing the quality of learning, especially in rural areas such as Sugarang Bayu Village. This study aims to analyze the condition of educational facilities and infrastructure in the village and identify the efforts that have been made and can be undertaken to improve them. The research employs a qualitative approach with data collection techniques including observation, interviews, and document analysis. The findings reveal that educational facilities in Sugarang Bayu Village remain limited, particularly in terms of classroom availability, laboratories, libraries, and access to educational technology. The primary challenges include budget constraints and limited support from policymakers. However, initiatives from the community and schools have emerged to address these issues, such as fundraising and collaboration with governmental and non-governmental organizations. Therefore, synergy between the government, the community, and the private sector is essential to ensure sustainable improvements in educational infrastructure. By enhancing educational facilities, the quality of learning and students' academic performance in Sugarang Bayu Village is expected to improve, ultimately fostering a more competitive human resource base.